Validation of the Return To Work Self‐Efficacy questionnaire in a population of employees undergoing treatment for cancer. (20th November 2020) - Rosbjerg, Rikke; Hansen, Dorte Gilså; Zachariae, Robert; Stapelfeldt, Christina Malmose; Hoejris, Inger; Rasmussen, Mathias Tvilling; Drysdale, Susanne Wiben; Labriola, Merete
Abstract: Objective: Several Return To Work Self‐Efficacy (RTWSE) questionnaires have been developed and found relevant to understanding the return to work (RTW) process of employees with various health problems, including employees with cancer. The aim of the present study was to examine the reliability and validity of the Danish 19‐item RTWSE questionnaire (RTWSE‐19 DK ) in a sample of employees with cancer. Methods: Employees undergoing treatment for cancer completed the RTWSE‐19 DK at baseline ( n  = 68) and at 1 week ( n  = 49). Additional questionnaires measured work ability, cancer‐related self‐efficacy and psychological distress. Internal consistency, test–retest reliability and construct validity were examined. Results: The total and the three subscales of the RTWSE‐19 DK showed good internal consistencies with Cronbach's alphas between 0.90 and 0.97 and high test–retest reliability with Intraclass Correlation Coefficients between 0.84 and 0.90. Examining construct validity, the RTWSE‐19 DK showed medium and large correlations with cancer‐related self‐efficacy ( r  = 0.54), mental work ability ( r  = 0.51), and general work ability ( r  = 0.35), small correlations with physical work ability ( r  = 0.26) and anxiety ( r  = −0.10), and no correlations with depression ( r  = −0.08) and test date ( r  = 0.03). Conclusion: The RTWSE‐19 DK showed good reliability and adequate validity in employees undergoing cancer treatment. In clinical practice, the RTWSE‐19 questionnaire may help practitioners identify areas of concern in the RTW process of cancer patients.